Evolution of a Tumorigenic Property Conferred by Glycophosphatidyl-Inositol Membrane Anchors of Carcinoembryonic Antigen Gene Family Members during the Primate Radiation - Naghibalhossaini, Fakhraddin (The American Society for Cell Biology, 2007)
GPI membrane anchors of cell surface glycoproteins have been shown to confer functional properties that are different from their transmembrane (TM)-anchored counterparts. For the human carcinoembryonic antigen (CEA) family, a subfamily of the immunoglobulin superfamily, conversion of the mode of membrane linkage from TM to GPI confers radical changes in function: from tumor suppression or neutrality toward inhibition of differentiation and anoikis and distortion of tissue architecture, thereby contributing to tumorigenesis. We show here that GPI anchorage in the CEA family evolved twice independently in primates, very likely from more primitive TM anchors, by different packages of mutations. Both mutational packages, one package found in many primates, including humans, and a second, novel package found only in the Cebidae radiation of New World monkeys, give rise to efficiently processed GPI-linked proteins. Both types of GPI anchors mediate inhibition of cell differentiation. The estimated rate of nonsynonymous mutations (K(a)) in the anchor-determining domain for conversion from TM to GPI anchorage in the CEA family that were fixed during evolution in these primates is 7 times higher than the average K(a) in primates, indicating positive selection. These results suggest therefore that the functional changes mediated by CEA GPI anchors, including the inhibition of differentiation and anoikis, could be adaptive and advantageous.